Validation of Autism Diagnosis and Clinical Data in the SPARK Cohort. - Fombonne, Eric; Coppola, Leigh; Mastel, Sarah; O'Roak, Brian J. (Journal of Autism & Developmental Disorders, 2022)
The SPARK cohort was established to facilitate recruitment in studies of large numbers of participants with autism spectrum disorder (ASD). Online registration requires participants to have received a lifetime professional diagnosis by health or school providers although diagnoses are not independently verified. This study was set to examine the validity of self- and caregiver-reported autism diagnoses. Electronic medical records (EMR) of 254 SPARK participants (77.6% male, age 10.7 years) were abstracted. Using two different methods, confirmation of ASD diagnosis in EMRs was obtained in 98.8% of cases. Core clinical features recorded in EMRs were typical of autism samples and showed very good agreement with SPARK cohort data, providing further evidence of the validity of clinical information in the SPARK database.